Characterisation of the Average Worker Employed Under Flexible Forms of Employment –Report on the Study of Individual Differences in the Context of Sociodemographic DataConcerning Polish Workers - Dobrowolska, Małgorzata; Paruzel-Czachura, Mariola; Stasiła-Sieradzka, Marta; Sikora, Jagoda (European Journal of Economics and Business Studies, 2018)
The paper presents the sociodemographic data obtained as a result of an empirical study carried out on a groupof n=2118 workers employed under what is referred to as flexible forms of employment, within a more extensiveresearch project entitled “Occupational problems of individuals working under flexible forms of employment –the psychological perspective”. The inspiration to focus on this particular part of the research was provided bya trend observed in the international literature, analysing the profile of an average flexible worker in highlydeveloped countries. An analysis of the study sample of flexible workers shows that the group included ratheryoung people, with a similar share of women and men, living in big cities, and with a rather short length ofservice; they were well-educated, married people with children, with a small number of previous employers,and mostly working in the private sector. The Polish study sample matches the descriptions of the averageflexible European worker.
Keywords: workers employed under flexible forms of employment, sociodemographic data, worker profile, individual differences